SISTEM PEMANTAUAN KETINGGIAN AIR SUNGAI DENGAN PENDEKATAN JARINGAN NIRKABEL - Eva Itma Anna; Khozainuz Zuhri (Universitas Mitra Indonesia, 2020)
AbstractAlmost every rainy season, areas that are near watershed areas or watersheds. The area along the river has an important role in contributing and has a very high level of urgency to the occurrence of floods. Floods that often come suddenly cause huge losses, so people cannot be prepared to face flood disasters. So far the information system that has been built has been widely applied, but it has not maximally reduced the losses. To solve this problem, it is necessary to have a model or concept of a watershed monitoring information system that is fast and easily accessible online through a web application. In addition to some of the above, the concept of a communication system between the device point (node) to the center (server) along the river flow is made wirelessly using the ZigBee protocol. The results of the study are a wireless network based water level monitoring system that can be used as a basis for the next level of research.